Dead sea scrolls fragments in the Museum collection - Tov, Emanuel; Davis, Kipp; Duke, Robert R. (Publications of Museum of the Bible,, 2016)
This volume contains thirteen previously unpublished Dead Sea Scrolls fragments, twelve Hebrew Bible fragments and one non-biblical fragment, presented with the full scholarly apparatus and advanced reconstruction techniques. The books from the Hebrew Bible are Genesis, Exodus, Leviticus, Numbers, Jeremiah, Ezekiel, Jonah, Micah, Psalms, Daniel, and Nehemiah. The latter is an especially important addition to known material. The non-biblical fragment probably represents a new copy of 4QInstruction. The work on these fragments was conducted under the auspices of the Museum of the Bible Scholars Initiative, whose mission is to publish research conducted collaboratively by scholar-mentors and students. The ultimate goal is to provide students with the opportunity to develop as scholars under the guidance of their scholar-mentors. N.B. In light of the ongoing discussion of the authenticity of several of the Dead Sea Scrolls fragments published in this first volume of the Publications of Museum of the Bible (Brill 2016), Brill is now able to provide access to an analysis of five of the fragments of the Dead Sea Scrolls. The material analysis of the fragments was carried out by the Bundesanstalt für Materialforschung and -prüfung (BAM). Further research and analysis will be made available as part of the ongoing research into the published fragments, including an investigation of the known provenance of the fragments.